Regional standards and local routes in adoption techniques for specialised terminologies in the dialects of written Arabic - Osama Youssef, Riham; Wilmsen, David (The Journal of Specialised Translation, 2009)
As opposed to its numerous, somewhat mutually unintelligible regional spoken vernaculars, formal written Arabic is generally regarded by its users as constituting a single standard across the entire Arab world. Regardless of this perception, translators and interpreters are aware that written Arabic also demonstrates regional variations. This poses potential obstacles to those working in a transnational environment, in that regional technical terminologies are for their part also somewhat mutually unintelligible. To assess the terminological variations in formal written Arabic, an examination was made of technical terms compiled from original works by Arab authors and western books translated into Arabic. Seventeen in all, these were the product of twelve Arab authors and translators writing or translating works in the fields of sociology and psychology. These fields were chosen precisely because they are among the fields outside of the Arab intellectual tradition, only being introduced to it relatively recently, being thus likely to employ novel terminologies. Terms extracted from these works were checked against 16 general and specialist dictionaries and three United Nations glossaries. Terminological discrepancies and inconsistencies were noticed in all of these works. Corroborating evidence is brought by observations of technical terms and regional variants in commercial jargon, journalistic usage, and municipal categories from Arab world.